Treatment of schizophrenia and bipolar disorder (ChAD) - a review of the literature - Jakub Klas; Natalia Kluz; Mikołaj Makaryczew; Klaudia Piwowar (Kazimierz Wielki University, 2021)
Introduction and aims of the study: The aim of this study is to present recent reports on the treatment and therapy of schizophrenia and bipolar disorder (ChAD). The current treatment of patients affected by these diseases is difficult and unsatisfactory, therefore it is necessary to find new therapeutic options that will improve the effectiveness of treatment For the purpose of this study, scientific papers were reviewed using the Google Scholar search engine covering studies from 2016 to 2021. A dozen papers covering the scope of the publication were selected. Results: In the treatment of schizophrenia, the use of cannabinoids is of greatest interest due to the action of the preparations on the endocannabinoid system. In the treatment of ChaD, promising reports have been published on the therapy with aripiprazole and the need to improve its use in the treatment of both akathisia and agitation. Furthermore, from the fact that abnormalities of calcium signalling are considered a possible pathophysiological process in ChAD, it has been suggested that calcium channel L antagonists may be potential therapeutic agents in bipolar affective disorder. One study also demonstrated the potential use of vortioxetine in the treatment of patients with a depressive episode. Conclusions: The results of recent studies on the treatment of schizophrenia and ChAD cited in this paper offer the prospect of creating treatment regimens that are more effective and targeted in the aforementioned diseases. However, further randomised trials are needed to confirm the effective use of the cited drugs in the treatment of these diseases.